2003
DOI: 10.1242/jcs.00478
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of early endocytic vesicle motility and fission in a reconstituted system

Abstract: We previously established conditions to reconstitute kinesin-dependent early endocytic vesicle motility and fission on microtubules in vitro. The present study examined the question whether motility and fission are regulated in this system. Screening for proteins by immunofluorescence microscopy revealed that the small G protein, Rab4, was associated with 80% of hepatocyte-derived early endocytic vesicles that contain the ligand asialoorosomucoid (ASOR). By contrast, other markers for early endocytic vesicles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
82
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(92 citation statements)
references
References 56 publications
9
82
1
Order By: Relevance
“…In vitro studies of endocytic vesicles from rat liver indicated an involvement of the minus-end-directed kinesin, KIFC2 (REF. 61). However, KIFC2-knockout mice are viable and reproduce normally, arguing against a crucial role of KIFC2 for cell viability 62 .…”
Section: Box 2 | Modes Of Motor-cargo Associationmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro studies of endocytic vesicles from rat liver indicated an involvement of the minus-end-directed kinesin, KIFC2 (REF. 61). However, KIFC2-knockout mice are viable and reproduce normally, arguing against a crucial role of KIFC2 for cell viability 62 .…”
Section: Box 2 | Modes Of Motor-cargo Associationmentioning
confidence: 99%
“…Uploading of endosomes onto dynein is dependent on dynactin and LIS1 (a dynein activator that is defective in patients with the brain disorder lissencephaly 77,78 ), which both accumulate at microtubule plus ends. The functional significance of bidirectional endosome movement needs to be clarified, but it might be either to keep these organelles dispersed in the cytoplasm 79 , to enhance encounters between different compartments for subsequent fusion 68 , or to support fission 61 .…”
Section: Box 2 | Modes Of Motor-cargo Associationmentioning
confidence: 99%
“…Using these tools, we found that plus-end motility of early endocytic vesicles from rat liver was mediated by the conventional kinesin Kif5B (standardized nomenclature kinesin-1) (Miki et al, 2003(Miki et al, , 2005Lawrence et al, 2004), and minus-end motility was mediated by Kifc2 (standardized nomenclature kinesin-14B) (Bananis et al, , 2003(Bananis et al, , 2004Murray et al, 2000). Whereas Kifc2 was initially described as a brain-specific minus-enddirected kinesin Saito et al, 1997), our studies showed that it was highly associated with these vesicles prepared from rat liver (Bananis et al, 2003). Although the rat is a convenient experimental animal, the power of genetic models that have been established in the mouse led us, in the present study, to examine microtubulebased motility and processing of early endocytic vesicles derived from mouse liver.…”
mentioning
confidence: 99%
“…Motility assays were performed in a 3-l chamber consisting of two pieces of double-sided tape sandwiched between optical glass as described previously (Murray et al, 2002). The chamber was coated with 0.03 mg/ml DEAE-dextran (GE Healthcare), and rhodamine-labeled, Taxol-stabilized microtubules were added and incubated for 3 min at room temperature (Bananis et al, , 2003(Bananis et al, , 2004. The chamber was washed three times with PMEE motility buffer (35 mM PIPES-K 2 , 5 mM MgCl 2 , 1 mM EGTA, 0.5 mM EDTA, 4 mM DTT, 20 M Taxol, and 2 mg/ml BSA) containing 5 mg/ml casein followed by three washes with PMEE motility buffer without casein.…”
mentioning
confidence: 99%
See 1 more Smart Citation